The effect of Strategy-based Instruction on Medical Students' Academic Writing Performance - Yusef Rajabi (Mashhad University of Medical Sciences, 2021)
Background: The present study was intended to investigate the effectiveness of strategy-based instruction in the form of self-regulatory strategy development on persuasive academic writing performance of a group of Iranian medicine and pharmacy students. Additionally, the study sought to examine if such instruction carries over to a related academic genre, i.e., descriptive writing.Methods: First, 30 male and female medicine and pharmacy students were administered pre-tests on target genres. Secondly, they received SBI on the persuasive genre of academic writing. Thirdly, the participants were asked to write essays on a set of writing probes across these two genres. Finally, post-tests were administered.Results: The results showed that the persuasive-specific self-regulatory strategy instruction the participants received contributed to their performance on persuasive academic writing. In the case of descriptive academic genre, the participants' performances on the posttest experienced a boost compared to those in the pretest corroborating the transfer of learning to a related non-instructed genre. More specifically, the sentences participants wrote in the posttests were longer, qualitatively better, and contained more persuasive and descriptive elements.Conclusions: Supplementing English for academic purposes courses for the students of medicine with strategy-based instruction in the form of genre-specific self-regulatory strategy development interventions seems a necessary first step in enhancing academic writing ability of medical students. The findings out of this research have certain implications for English for academic purposes students and teachers accordingly.